2021
DOI: 10.3406/mcarh.2021.2202
|View full text |Cite
|
Sign up to set email alerts
|

The Lower Palaeolithic assemblage of Medzhibozh 1 layer III (Ukraine) and its palaeoenvironmental context

Abstract: The main focus of this paper is to present the stone assemblage of one of the Lower Palaeolithic layers of Medzhibozh 1. Detailed typological and technological characteristics of the stone industry of layer III of the locality Medzhibozh 1 are given against the background of geomorphological characteristics and features of the Quaternary structure of the area. Medzhibozh 1 represents one of several multi-layered sites of Lower Palaeolithic age on the Upper Bug, among which are also Medzhibozh A, Golovchintsy 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…400 kya) are corroborated with biostratigraphic data for the layer 16a (Qi et al, 2018). At the same time, geomorphological data allow suggesting an MIS 15-13 age for sediments containing artefacts of layer III (Stepanchuk et al, 2021).…”
Section: Stratigraphy and Agesupporting
confidence: 70%
See 1 more Smart Citation
“…400 kya) are corroborated with biostratigraphic data for the layer 16a (Qi et al, 2018). At the same time, geomorphological data allow suggesting an MIS 15-13 age for sediments containing artefacts of layer III (Stepanchuk et al, 2021).…”
Section: Stratigraphy and Agesupporting
confidence: 70%
“…2), some of which (in particular, layers 15 and 16) comprise stone tools and other signs of ancient human activity at the site, and are equal to the so-called layer 16a (i.e. cultural horizon) sensu Stepanchuk and Moigne (2016) or layer III sensu Stepanchuk et al (2021). A pedological study (Matviishina et al, 2013) revealed the presence of Middle and Upper Pleistocene loess and soil sediments (Stepanchuk and Moigne, 2016: fig.…”
Section: Stratigraphy and Agementioning
confidence: 99%